Application of Product Branding to Increase the Effectiveness of MSME Marketing (Mangrove Drinks and Onion Chips) in Kwala Langkat Village - Ramadhan, Achmad; Harahap, Ananda Aditya Sari; Lubis, Nurul Amanda Khairani; Andini, Rizka Tri; Sari, Anita Purnama; Aini, Siti (International Journal Of Education, Social Studies, And Management (IJESSM), 2024)
In the era of globalization in marketing communications, there are many strategies that can be used, one of which is product branding, namely the strategy or process of building a unique identity and value for MSME products. So it can be differentiated from other competitors and attract consumer interest. This research article aims to analyze product branding in increasing the marketing effectiveness of MSMEs in Kwala Langkat Village. The results of this research show that the application of logos, slogans and product packaging has a big impact on sales of mangrove drink products and onion chips in Kwala Langkat Village; awareness of the residents of Kwala Langkat Village to play a full role in improving branding on products sold to become products that are ready to compete and attract consumers; Product branding is the right strategy and increases the effectiveness and competitiveness of MSMEs in Kwala Langkat Village.